2021
DOI: 10.1002/ccd.29526
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter pulmonary denervation in patients with left heart failure with reduced ejection fraction and combined precapillary and postcapillary pulmonary hypertension: A prospective single center experience

Abstract: Objectives: The present study was a prospective, single-center, single-arm study to investigate the efficacy of transcatheter pulmonary artery denervation (TPADN) in patients with combined postcapillary and precapillary PH (Cpc-PH) associated with left heart failure with reduced ejection fraction (HF-rEF).Background: Pulmonary hypertension (PH) in patients with left ventricular systolic dysfunction has a negative impact on outcome. Methods:The combination of pulmonary artery systolic pressure (PAPs) ≥60 mmHg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Cardiac index (CI) was unchanged between baseline and repeat RHC (2.24 [1.90, 2.67] vs. 2.46 [1.98, 2.91] L/min/m 2 , p = 0.1) in those who progressed to Cpc-PH. Conversely, mPAP (33 [29,37] vs. 40 [33,44] mmHg, p < 0.001), PVR (1.99 [1.63, 2.41] vs. 3.88 [3.49, 4.72] WU, p < 0.001), RA pressure (9 [6,15] vs. 14 [10,19] mmHg, p < 0.01), and the diastolic pressure gradient (DPG, −1 [−3, 2] vs. 4 [1,7] mmHg, p < 0.001) increased in this group. These changes resulted in a 26% increase in mPAP and 11% decrease in CI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac index (CI) was unchanged between baseline and repeat RHC (2.24 [1.90, 2.67] vs. 2.46 [1.98, 2.91] L/min/m 2 , p = 0.1) in those who progressed to Cpc-PH. Conversely, mPAP (33 [29,37] vs. 40 [33,44] mmHg, p < 0.001), PVR (1.99 [1.63, 2.41] vs. 3.88 [3.49, 4.72] WU, p < 0.001), RA pressure (9 [6,15] vs. 14 [10,19] mmHg, p < 0.01), and the diastolic pressure gradient (DPG, −1 [−3, 2] vs. 4 [1,7] mmHg, p < 0.001) increased in this group. These changes resulted in a 26% increase in mPAP and 11% decrease in CI.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] Distinguishing Cpc-PH from Ipc-PH is important because the former group has worse outcomes 7 and therapies targeted at Cpc-PH are only in the preliminary stages. [8][9][10][11][12][13] Cross-sectional studies have reported the hemodynamic, 5,14 pathologic, 15,16 genetic, 4,17 and cellular changes [18][19][20] behind the pathophysiology of PH-LHD and Cpc-PH, but it remains unclear why some patients transition from Ipc-PH to Cpc-PH, while others remain with Ipc-PH. Although no prior studies describe a conversion from Ipc-PH to Cpc-PH and the development of Cpc-PH at onset of PH-LHD could be possible, the currently accepted pathophysiology of Cpc-PH begins with long-standing elevation in left-sided pressures, which suggests that development of Ipc-PH should precede Cpc-PH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small feasibility trials have demonstrated benefit in the PAH and chronic thromboembolic pulmonary hypertension populations [31,32]. A single center series of PADN in 10 patients with HFrEF and CpcPH found a significant reduction in PVR in five patients, from mean 7.2 to 3.7 Woods units at 6 months of follow-up [33]. There was no significant change in the PCWP, and intriguingly right atrial pressure improved as well suggesting improvement in right heart function.…”
Section: Clinical Trialsmentioning
confidence: 99%